Znaczenie polskiego wschodniego pogranicza kulturowego dla poszerzania zasięgu zachodniej cywilizacji w XVI-XIX w. = The significance of the Polish eastern cultural borderland for the expansion of the western civilization in the 16th-19th centurie - Topolska-Piechowiak, Maria Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the considerations is to present the expansion of the cultural borderland, of insular nature (until the end of the 15th century), in the central part of the Grand Duchy of Lithuania (Lithuanian and Belorussian lands) and Halick - Vladimir lands (one century earlier). The earliest impact was observed in the north in the German borderland, whereas the Byzantine and Russian in?uence was visible in other areas. In the Middle of the 17th century in result of the missionary work of the Catholic Church, Reformation churches and the Greek Catholic church the cultural borderland reached the Dnieper areas along the new borderline with Russia. Both Polish and western culture radiated to Russia as well. The borderline performed the role of a center in the 17th century. Whereas after the ?rst partition of Poland it functioned as the borderland of the western and Polish culture for the ethnic Russia.
Keywords: pogranicze wschodnie; Polska; Litwa; Rosja; Białoruś; Ukraina; 16-19 w.